Speaking Activities Implemented by English Teachers at SMPN 1 Padang - Fitriyana, Tari; Kher, Dinovia Fannil (Universitas Negeri Padang, 2025)
This research aims to describe various speaking activities used by English teachers at SMPN 1 Padang, how the implementations, as well as challenges or problems do English teachers face in implementing them. The design of this research is descriptive qualitative. The instruments of this research are interview guidelines and observation sheets. The data collected through interviews and observations with two English teachers at SMPN 1 Padang. The finding shows that there are several speaking activities used, such as Questionnaires, Communication Games, Simulation and Roleplay, Prepared Talks, and Storytelling. The implementation of these speaking activities matches the characteristics of each speaking activity according to experts. These findings also show that some challenges or problems are faced by English teachers in implementing the speaking activities. There are inhibitions and low or uneven participation.